Antibiotic Susceptibility Pattern and Detection of Meca Gene in Methicillin Resistant Staphylococcus Epidermidis Isolated from Wards Surfaces of Kampala International University Teaching Hospital, Uganda - Adam, Abubakar S.; Micheni, Lisa; Onkoba, Sarah K.; Ntulume, Ibrahim; Aliero, Adamu A.; Namatovu, Alice (Romanian Archives of Microbiology and Immunology, 2020)
Staphylococcus epidermidis is a Gram positive, coagulase-negative staphylococcus that frequently causes device- or surgery-associated nosocomial infections worldwide. Drug-resistant strains such as methicillin resistant S. epidermidis (DR-SE) have been reported with serious clinical implications. Objectives: This study determined the percentage of S. epidermidis from wards surfaces of Kampala International University-Teaching Hospital (KIU-TH), the drug susceptibility patterns of the isolates and searched for mecA gene among Cefoxitin resistant isolates. Materials and Methods: A total of three hundred sixty-three (363) swab samples were collected from floors, door knobs and walls from different wards. S. epidermidis was identified after subjecting the samples to five tests including growth on mannitol salt agar, catalase, coagulase, Desferrioxamine and Fosfomycin tests. Susceptibility patterns of all the S. epidermidis isolates identified were tested against Amikacin, Cefazolin, Trimethoprim-Sulfamethoxazole, Ciprofloxacin, Gentamycin and Cefoxitin using the disc diffusion method. All the isolates resistant to Cefoxitin were analysed for the presence of mecA gene using the conventional polymerase chain reaction (PCR) method. Results: One hundred and twelve 112 (30.8%) strains of S. epidermidis were isolated from 363 samples collected. Out of 112 S. epidermidis isolates, 11 (9.8%) were found resistant to Cefoxitin and all Cefoxitin resistant isolates (100%) were found to have the mecA gene, while 89.3% of the strains were found non-susceptible to Trimethoprim-Sulphamethoxazole. Conclusion: This study found that S. epidermidis is present on wards surfaces of KIU-TH. S. epidermidis isolates harboured Trimethoprim-Sulfamethoxazole resistance in a high percent. All the isolates resistant to Cefoxitin were positive for the mecA gene. Taking into consideration the high rate of Trimethoprim-Sulphamethoxazole non-susceptibility, Cefazolin, Cefoxitin, Gentamycin and Amikacin are recommended as a better prescription for managing infections caused by S. epidermidis resistant to commonly used antibiotics in the studied area.
Keywords: S. epidermidis; Ward surfaces; Cefoxitin; mecA gene; Trimethoprim-Sulphamethoxazole